Aplikasi Pengolahan Data dan Layanan Pada BAZNAS (Badan Amil Zakat Nasional) Kota Parepare - Yunus, Mughaffir; Alam, Syahirun; Al-Mugtadir, Muhammad (Fakultas Teknik Universitas Muhammadiyah Parepare, 2021)
Zakat, infaq, and alms are parts of religious mechanisms that are based on the spirit of equal distribution of income. Therefore, the majority of Indonesians who are Moslems and are culturally obliged to give zakat. BAZNAS then seeks to create a management information system that can help BAZNAS and LAZ operations in a management information system that can produce tiered reports from city to province, province to center, and central to The President, through the Ministry of Religion, needs quality information, that is relevant, accurate and timely so that the right decisions can be made in accordance with the information system implemented by the amil zakat agency. Information system of all data processing in the amil zakat body can be stored neatly and not done manually so that work can be done efficiently and does not need a long time. This Application can make it easier for BAZNAS employees in making financial reports with this application making it easier for the public to access information about BAZNAS of Parepare City and make it easier for people to channel their zakat funds so that they no longer need to meet each other. advance or pay for it directly.